A comprehensive review on food waste anaerobic digestion: Research updates and tendencies. (January 2018) - Ren, Yuanyuan; Yu, Miao; Wu, Chuanfu; Wang, Qunhui; Gao, Ming; Huang, Qiqi; Liu, Yu
Highlights: Research status and trends over 25 years were analyzed by bibliometric analysis. Focuses on pretreatment, co-digestion, and process optimization were reviewed. Ethanol and aerobic prefermentation as new pretreatment methods were clarified. Biorefinery and new anaerobic digestion model will be new research directions. Abstract: Anaerobic digestion has been practically applied in agricultural and industrial waste treatment and recognized as an economical-effective way for food waste disposal. This paper presented an overview on the researches about anaerobic digestion of food waste. Technologies (e.g., pretreatment, co-digestion, inhibition and mitigation, anaerobic digestion systems, etc.) were introduced and evaluated on the basis of bibliometric analysis. Results indicated that ethanol and aerobic prefermentation were novel approaches to enhance substrates hydrolysis and methane yield. With the promotion of resource recovery, more attention should be paid to biorefinery technologies which can produce more useful products toward zero emissions. Furthermore, a technological route for food waste conversion based on anaerobic digestion was proposed.